The Readiness of Nahdlatul Ulama Surabaya University (UNUSA) to Be the Centre of Development of Rahmatan Lil Alamin Entrepreneur (EnPlus) - Mohamad Yusak Anshori (Jurnal Bisnis dan Keuangan, 2020)
Brush (2014) states that to make the student having the spirit of entrepreneurship they have to develop start-ups in term of realizing a university venture and also to give benefit for the society, therefore, an ecosystem that is called Entrepreneurship Education Ecosystem is needed. UNUSA is one of the universities in Indonesia that has a strong vision to prepare a generation having spirit of Rahmatan Lil Alamin entrepreneurship based on Islamic values. The objective of this paper is to describe the readiness of UNUSA to be a university with Islamic values under the Nahdlatul Ulama organization to be the Entrepreneurship Ecosystem from the aspect of Brush’s theory (2014). From the result of this discussion it is find out that in spite of only six years old in age UNUSA has some breakthroughs to develop the entrepreneurship education ecosystem. However, it is urgent for Unusa to develop Business Incubator seeing that the number of UNUSA students are more and more from years to years. Such fact can not be separated from the mission of UNUSA to be the centre of entrepreneurs development and building in Indonesia. It can be concluded that UNUSA is ready to become the centre of Rahmatan Lil Alamin entrepreneur development and building and will support the government program of One Pesantren One Product (OPOP)